STUDY OF MASS TRANSFER OF HYDROGEN SULFIDE IN THE "GAS - LIQUID" - , А. А.; , И. Л.; , Э. А. (Municipal economy of cities. Series: «Economy science», 2013)
The factors influencing the mass transfer of hydrogen sulfide in the gaseous medium. The results of the investigation of the laws of mass transfer of hydrogen sulfide in the "gas-liquid". The equation for calculating the intensity of mass transfer of hydrogen sulphide from the liquid phase in the space podsvodovoe sewer.